PRECISE POSITIONING OF DIAMAGNETICALLY LEVITATED MICROROBOT - Demircali, Anil; Uvet, Huseyin; Kahraman, Yusuf; Kose, Tunc; Sisu, Serhat; Erkan, Kadir (CENTRAL BOHEMIA UNIV, 2017)
In this article, we present a microrobot manipulation technique with high precision positional ability to move in a fluid environment with diamagnetic levitation. Untethered manipulation of microrobots by means of externally applied magnetic forces has been emerging as a promising field of research, particularly due to its potential for medical and biological applications. The decreased size of the robots makes them suitable for both in vitro applications such as sorting, moving, filtering micro particles (e.g. cells) within lab-on-a-chip platforms and in vivo applications such as minimally invasive surgeries or targeted drug delivery inside a human body. Precise (nano) positioning of the levitated microrobot on the pyrolytic graphite is demonstrated in the liquid. Positioning is achieved by the movement of a lifter magnet on the sensitive microstage. The suspended microrobot successfully tracked the identified roots. Our study is about controlling the microrobot suspended on the pyrolytic graphite with nano-precision via fixed lifting magnets. The purpose of the presented method is to eliminate the friction force between the surface of the substrate and the microrobot. Thus, high accuracy motion can be achieved.
Keywords: Microrobots; Magnetic Levitation; MOTION; Business & Economics; Public Administration